Demographic and Clinical Profiles of Children with Celiac Disease Attending Paediatrics Department of Bangladesh Medical University - Parveen, Shohely; Sarker, Mst Naznin; Islam, M M Shahin Ul; Hasan, Md Shariful; Rahman, Md Zahidur (Faridpur Medical College Journal, 2026)
Background: Coeliac disease (CD) is an autoimmune disorder triggered by gluten in genetically predisposed individuals. While traditionally associated with Western populations, CD is increasingly recognized in South Asia, including Bangladesh. Materials & Methods: A descriptive, cross sectional study was conducted at BMU from July 2022 to June 2025 to see demographic and clinical profiles of celiac disease in our country. A total of 62 children (age <18 years) attending the Paediatrics department of BMU with suspected celiac disease were initially enrolled for the study. Out of 62 children with suspected celiac disease, 35.5% (22) were positive for IgA anti-tTG and were finally included in the study to find out their demographic and clinical profiles. Results: Among studied children female were 31.81% and male 68.18%. Mean age of all children with tTG positive group was 10.30 ± 4.10. The age group, 10-14 year showed the highest (50%) prevalence of positive anti-tTG. Maximum (63.64%) children came from middle income class family. The common presentation among the positive anti-tTG (IgA) children seen were chronic diarrhea (90.90%), followed by abdominal pain (68.18%), abdominal distension (54.54%), feeling of gas accumulation in the abdomen (45.45%), weight loss (22.72%) and vomiting (18.18%). Unexplained failure to thrive was present in 8(36.3%) patients. Four (4) patients (18.18%) were with short stature, anemia was present in 6 patients (27.27%). Among 22 seropositive patients, histological changes compatible with CD were found in 19 (86.3%) cases and normal in 3 cases. Conclusion: In conclusion, Screening for celiac disease may be included in diagnostic tests for evaluating children presented with chronic diarrhea, abdominal pain and/or short stature. Faridpur Med. Coll. J. 2026;21(1):07-11